1992
DOI: 10.1002/1097-0142(19921015)70:8<2061::aid-cncr2820700808>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic flow in carcinoma of the head of the pancreas

Abstract: The lymphatic pathway from the head of the pancreas to the para‐aortic lymph nodes was examined on the basis of the frequency of lymph node involvements. Forty‐four patients were examined. All patients had extended radical operations. Thirty‐one of 44 (70.5%) patients had lymph node involvement. The lymph nodes that had a high metastatic rate included the following: (1) lymph nodes around the common hepatic artery (number 8 lymph node); (2) lymph nodes of the hepatoduodenal ligament (number 12 lymph node); (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 3 publications
4
46
0
2
Order By: Relevance
“…Concerning the paraaortic lymph nodes (Group 16), pathologic reports [25,26,31,33] showed that the majority of positive lymph nodes was in the areas between the celiac artery and the inferior mesenteric artery, wherever the primary tumors were situated. Therefore, only this area was included in the contouring (red area, Figures 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the paraaortic lymph nodes (Group 16), pathologic reports [25,26,31,33] showed that the majority of positive lymph nodes was in the areas between the celiac artery and the inferior mesenteric artery, wherever the primary tumors were situated. Therefore, only this area was included in the contouring (red area, Figures 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…12a, 12b and 12c because 86.6% of the available reports on the rate of metastases to station 12 come from Authors who resect Nos. 12a, 12b, 12c, 12h and 12p [14,31,32,56,62,64,66,67]. Removing 12h and 12p is best avoided because it carries the risk of the common bile duct stump being inadequately vascularized.…”
Section: Proposal For a Standard Lymphadenectomymentioning
confidence: 99%
“…Details for lymph node stations 12 and 14 (drawn from papers not included in the above table because they report on partly overlapping case series): station 12a: 0%, 12b:19%, 12c: 0%; 12d: 2.4%; station 14a: 19%, 14b: 26.2%, 14c: 7.1%, 14d:14.3% -from Nagakawa[67] station 14a: 18.2%, 14b: 20.5%, 14c: 6.8%; 14d: 13.6% -from Kayahara[66]. * Stations 7 and 10 were not included in the table due to the very low incidence of metastasis.Data in the National Pancreatic Cancer Registry Committee of the Japanese Pancreatic Society 1981-1990. à Calculated on only 82 reported patients.…”
mentioning
confidence: 99%
“…Pancreatic cancer is a highly metastatic cancer characterized by widespread intraperitoneal dissemination and ascites formation, which frequently occur even after curative resection and constitute the major cause of death in pancreatic cancer patients (1,2). Therefore, the suppression of dissemination is an important issue in the treatment of pancreatic cancer.…”
mentioning
confidence: 99%